The Prognostic Value of 18F-FDG Uptake Ratio Between the Right and Left Ventricles in Idiopathic Pulmonary Arterial Hypertension. (November 2015) - Li, Wen; Wang, Lei; Xiong, Chang-Ming; Yang, Tao; Zhang, Yan; Gu, Qing; Yang, Yong; Ni, Xin-Hai; Liu, Zhi-Hong; Fang, Wei; He, Jian-Guo
<x xml:space="preserve">Abstract</x> Purpose Metabolic changes occur in the right ventricle (RV) under increased afterload in pulmonary arterial hypertension. FDG PET imaging has potential to assess RV function. In this study, we aimed to determine the prognostic value of metabolic changes of RV using FDG PET imaging in idiopathic pulmonary arterial hypertension (IPAH). Patients and Methods In this prospective investigation, patients newly diagnosed with IPAH were recruited. Patients underwent right heart catheterization, FDG PET imaging, and cardiac MR (CMR) within 1 week. Right ventricle hemodynamics, glucose metabolism derived from the FDG uptake levels, and functional parameters were obtained. The FDG uptake ratio between the RV and the left ventricle (LV) and its relation with the patients' survival were analyzed. Results A total of 45 IPAH patients were enrolled in this study, which included 13 male (28.9%) and 32 female (71.1%). The median follow-up time of this study was 1043 days. At the end of the follow-up, 36 patients survived, whereas 9 patients were deceased because of right heart failure. Multivariate Cox proportional hazard analysis showed that the ratio between the corrected RV and LV FDG uptake (cRV/LV) in both glucose-loading (cRV/LVg) and fasting (cRV/LVf) conditions independently predicted the mortality after adjusting for pulmonary vascular resistance index, mean right atrial pressure, and World Health Organization functional class. Kaplan-Meier survival analysis showed that patients with cRV/LVf greater than 143.65% in fasting condition (log rank, P = 0.030) or cRV/LVg greater than 120.55% in glucose-loading condition (log rank, P = 0.014) had worse prognosis. Conclusions The FDG uptake ratio between the RV and LV can be an independent predictor for long-term prognosis of IPAH patients.